Dynamically Modulated GaN Whispering Gallery Lasing Mode for Strain Sensor. (12th August 2019) - Peng, Yiyao; Lu, Junfeng; Peng, Dengfeng; Ma, Wenda; Li, Fangtao; Chen, Qiushuo; Wang, Xiandi; Sun, Junlu; Liu, Haitao; Pan, Caofeng
Abstract: The continuous development of strain sensors offers significant opportunities for improving human–machine interfaces and health monitoring. The dynamically modulated lasing mode is a novel approach to realize a flexible, noncontact, high color‐resolvability, high‐resolution, and ultrasensitive strain sensor. Here, a flexible strain sensor perceiving stress variations is reported via the dynamical regulation of a GaN whispering gallery lasing mode based on the piezoelectric effect. The refraction index of GaN shows a linear relationship with the applied external tensile strain, resulting in a redshift phenomenon of the lasing mode peak at room temperature due to the predominant function of the piezoelectric polarization in the GaN microwire. Compared with a strain sensor relying on the wavelength shift of a photoluminescence (PL) emission peak, the differences and advantages of a sensor based on the strain‐induced lasing mode variation are also investigated and analyzed systematically. This strain sensor may serve as an essential step toward the color mapping of mechanical signals by optical methods, with potential applications in color‐perceived touching sensing, noncontact stress measurement, laser modulation, and optical communication technologies. Abstract : A novel approach for dynamically modulating GaN‐based whispering‐gallery lasing mode through the piezoelectric polarization effect is proposed, which can not only regulate the optical signal but also be used as a strain sensor with advantages including high resolution, flexibility, noncontact interactions, good color‐resolvability, and simple construction. The experimental minimum resolution for the strain sensor reaches up to 0.16%.